Digital Da'wah Transformation of Nahdlatul Ulama: Religious Moderation Strategies in the Technological Era - Ahmad Nabil Annuha; Muhammad Yusuf Pratama (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2024)
NU's classical da'wah method, dominated by lectures, is often seen as less relevant in the modern era. Meanwhile, other religious groups have adopted da'wah approaches that are more suited to contemporary society. Seeing these conditions, it is necessary to update NU's da'wah strategy that integrates digital technology and the internet to spread the message of religious moderation more effectively. This research uses the literature study method to develop a new understanding and approach to religious moderation through digital da'wah. The main focus is examining how NU can utilize easy internet and digital media access in its da'wah strategy. The results of the study contribute to providing concrete solutions for technology-based da'wah methods, particularly in spreading the values of religious moderation that suit the conditions of modern Islamic society.   Metode dakwah klasik NU yang didominasi ceramah sering dipandang kurang relevan di era modern. Sementara itu, kelompok keagamaan lain telah mengadopsi pendekatan dakwah yang lebih sesuai dengan masyarakat kontemporer. Melihat kondisi tersebut, diperlukan pembaruan strategi dakwah NU yang mengintegrasikan teknologi digital dan internet untuk menyebarkan pesan moderasi beragama secara lebih efektif. Penelitian ini menggunakan metode studi pustaka untuk mengembangkan pemahaman dan pendekatan baru dalam moderasi beragama melalui dakwah digital. Fokus utamanya adalah mengkaji bagaimana NU dapat memanfaatkan kemudahan akses internet dan media digital dalam strategi dakwahnya. Hasil penelitian berkontribusi dalam memberikan solusi konkret untuk metode dakwah berbasis teknologi, khususnya dalam menyebarkan nilai-nilai moderasi beragama yang sesuai dengan kondisi masyarakat Islam modern.